Encouraging Students' Passion for Learning: The Effectiveness of Positive Reinforcement Techniques for Elementary School Students - Wahyu Rendiyono, Pramudya; Setiawan Wicaksono, Awang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Elementary schools play a crucial role as the foundation for children's academic and social development, particularly between the ages of six and twelve. Positive reinforcement is effective in reducing student absenteeism and tardiness. The objective of this research is to integrate theoretical understanding from lectures with practical skills in the field and to enhance student learning interest at Muhammadiyah Manyar Elementary School through the application of Positive Reinforcement Techniques. The research method uses a quasi-experimental design with pre-test and post-test aimed at improving the learning interest of fifth-grade students at Muhammadiyah Manyar Elementary School through the application of Positive Reinforcement Techniques. The research results indicate that positive reinforcement techniques have a significant effect on improving students' learning interest. All subjects experienced an increase in scores after the intervention, indicating that positive reinforcement can create a supportive environment for students to be more motivated to learn. The implications of this research are the need for adaptive and collaborative approaches in education, where reinforcement strategies not only enhance academic outcomes but also contribute to character development and shape individuals who are more confident and motivated to learn throughout their lives. Sekolah dasar berperan penting sebagai fondasi perkembangan akademik dan sosial anak-anak, khususnya pada usia enam hingga dua belas tahun. Penguatan positif efektif dalam menurunkan tingkat absensi dan keterlambatan siswa. Tujuan dari penelitian ini untuk mengintegrasikan pemahaman teoritis dari perkuliahan dengan keterampilan praktis di lapangan dan meningkatkan minat belajar siswa di SD Muhammadiyah Manyar melalui penerapan Teknik Reinforcement Positif. Metode Penelitian menggunakan eksperimen kuasi dengan desain pre-test dan post-test yang bertujuan untuk meningkatkan minat belajar siswa kelas 5 di SD Muhammadiyah Manyar melalui penerapan Teknik Reinforcement Positif. Hasil Penelitian Menunjukkan bahwa teknik reinforcement positif memiliki efek yang signifikan dalam meningkatkan minat belajar siswa. Seluruh subjek mengalami peningkatan skor setelah intervensi dilakukan, yang mengindikasikan bahwa reinforcement positif mampu menciptakan lingkungan yang mendukung bagi siswa untuk lebih termotivasi dalam belajar. Implikasi dari penelitian ini yaitu perlunya pendekatan adaptif dan kolaboratif dalam pendidikan di mana strategi reinforcement tidak hanya meningkatkan hasil akademis tetapi juga berkontribusi pada pengembangan karakter siswa dan membentuk individu yang lebih percaya diri dan termotivasi dalam belajar sepanjang hidup.